Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific - Pyle, Richard L.; Earle, John L.; Greene, Brian D. (Zootaxa, 2008)
Five new species of the damselfish genus Chromis 2 (Perciformes 3 : Labroidei 4 : Pomacentridae 5 ) are described from specimens collected from deep (>60 m) coral-reef habitat in the western Pacific by divers using mixed-gas closed-circuit rebreather gear. Two of the five new species (C. abyssus and C. circumaurea) are each described from specimens taken at a single locality within the Caroline Islands (Palau and Yap, respectively); one (C. degruyi) is described from specimens collected or observed throughout the Caroline Islands, and two (C. brevirostris and C. earina) are described from specimens collected from several localities throughout the Caroline Islands, Fiji, and Vanuatu. All five species can easily be distinguished from other known Chromis, and from each other, on the basis of color and morphology. These new species represent the first five scientific names prospectively registered in the official ICZN ZooBank registry 6 . Moreover, the electronic online edition of this document has been specially formatted with many embedded links to additional resources available online via the internet to enhance access to taxonomically-relevant information, and as a demonstration of the utility of international standards for biodiversity informatics.